Genetic analysis for combining ability in true seed crop of potato (Solanum tuberosum) - KUMAR, RAJ; KANG, G S (The Indian Journal of Agricultural Sciences, 2014)
Ninety populations from line x tester (15 x 6) design were studied for 6 characters in seeding and seedling-tuber crops of potato (Solanum tuberosum L.). Non-additive component was predominant in expression of various traits. 'EB/C 899','MS/82-638','JE 812','MS/82-797' abd 'EX/A 680-16' were found superiour parents in both crops based on their general combining ability for various traits. 'MS/82-638' x 'EX/A 680-16','MS 82-638' x 'MS/82-797','EB/C 899' x 'EX/A 680-16','Kufri Jyoti' x'Kufri Pukhraj','JE 812' x 'EX/A 680-16' and 'CP 2539' x 'EX/A 680-16' were superior crosses for developing high-yielding and uniform true seed populations.